Echinocandin B biosynthesis: a biosynthetic cluster from Aspergillus nidulans NRRL 8112 and reassembly of the subclusters Ecd and Hty from Aspergillus pachycristatus NRRL 11440 reveals a single coherent gene cluster. (December 2016) - Hüttel, Wolfgang; Youssar, Loubna; Grüning, Björn; Günther, Stefan; Hugentobler, Katharina
Abstract Background Echinocandins are nonribosomal lipopeptides produced by ascommycete fungi. Due to their strong inhibitory effect on fungal cell wall biosynthesis and lack of human toxicity, they have been developed to an important class of antifungal drugs. Since 2012, the biosynthetic gene clusters of most of the main echinocandin variants have been characterized. Especially the comparison of the clusters allows a deeper insight for the biosynthesis of these complex structures. Results In the genome of the echinocandin B producerAspergillus nidulans NRRL 8112 we have identified a gene cluster (Ani ) that encodes echinocandin biosynthesis. Sequence analyses showed thatAni is clearly delimited from the genomic context and forms a monophyletic lineage with the other echinocandin gene clusters. Importantly, we found that the disjunct genomic location of the echinocandin B gene cluster inA. pachycristatus NRRL 11440 on two separate subclusters, Ecd andHty, at two loci was likely an artifact of genome misassembly in the absence of a reference sequence. We show that both sequences can be aligned resulting a single cluster with a gene arrangement collinear compared to other clusters ofAspergillus sectionNidulantes . The reassembled gene cluster (Ecd /Hty ) is identical to a putative gene cluster (AE ) that was previously deposited at the NCBI as a sequence fromA. delacroxii NRRL 3860. PCR amplification of a part of the gene cluster resulted a sequence that was very similar (97 % identity), but not identical to that ofAE . Conclusions The Echinocandin B biosynthetic cluster fromA. nidulans NRRL 8112 (Ani ) is particularly similar to that ofA. pachycristatus NRRL 11440 (Ecd /Hty ).Ecd /Hty was originally reported as two disjunct sub-clustersEcd andHty, but is in fact a continuous sequence with the same gene order as inAni . According to sequences of PCR products amplified from genomic DNA, the echinocandin B producerA. delacroxii NRRL 3860 is closely related toA. pachycristatus NRRL 11440. A PCR-product from the gene cluster was very similar, but clearly distinct from the sequence published forA. delacroxii NRRL 3860 at the NCBI (No. AB720074). As the NCBI entry is virtually identical with the re-assembledEcd /Hty cluster, it is likely that it originates fromA. pachycristatus NRRL 11440 rather thanA. delacroxii NRRL 3860.